Diversity and evolution of the envelope gene of dengue virus type 1 circulating in India in recent times. (2015) - Dey, Sumanta; Nandy, Ashesh; Nandy, Papiya; Das, Sukhen
Dengue viral attacks have been reported in various parts of India in recent years. In this paper we report on our studies of the characterisation and evolutionary aspects of gene sequences of the envelope glycoprotein of the prevalent Indian dengue virus type 1. Comparison with sequences from other countries shows that the envelope genes identified in India are closely related to strains from Malaysia. From the evolutionary point of view the envelope gene sequences of this dengue virus of India for past few years show that a marked mutational shift in the nucleotide sequences of the envelope gene have taken place from around the year 2000. Also, phylogenetic relationship with other three sera of dengue virus reported in India from 2005 shows that the dengue virus 1 is more closely related to dengue viruses 3 and 4 and relatively distantly to dengue virus 2.